British Women's Writing from Brontë to Bloomsbury, Volume 1 1840s and 1850s (British Women's Writing from Brontë to Bloomsbury, 1840-1940,, 2018)
This five-volume series, British Women's Writing From Brontë to Bloomsbury, 1840-1940, historically contextualizes and traces developments in women's fiction from 1840 to 1940. Critically assessing both canonical and lesser-known British women's writing decade by decade, it redefines the landscape of women's authorship across a century of dynamic social and cultural change. With each of its volumes devoted to two decades, the series is wide in scope but historically sharply defined. Volume 1: 1840s and 1850s inaugurates the series by historically and culturally contextualizing Victorian women's writing distinctly within the 1840s and 1850s. Using a range of critical perspectives including political and literary history, feminist approaches, disability studies, and the history of reading, the volume's 16 original essays consider such developments as the construction of a post-Romantic tradition, the politicization of the domestic sphere, and the development of crime and sensation writing. Centrally, it reassesses key mid-nineteenth-century female authors in the context in which they first published while also recovering neglected women writers who helped to shape the literary landscape of the 1840s and 1850s.